Distinct pathways associated with chromosomal aberration frequency in a cohort exposed to genotoxic compounds compared to general population. (4th October 2019) - Niazi, Yasmeen; Thomsen, Hauke; Smolkova, Bozena; Vodickova, Ludmila; Vodenkova, Soňa; Kroupa, Michal; Vymetalkova, Veronika; Kazimirova, Alena; Barancokova, Magdalena; Volkovova, Katarina; Staruchova, Marta; Hoffmann, Per; et al.
Abstract: Non-specific structural chromosomal aberrations (CAs) observed in peripheral blood lymphocytes of healthy individuals can be either chromosome-type aberrations (CSAs) or chromatid-type aberrations (CTAs) depending on the stage of cell division they are induced in and mechanism of formation. It is important to study the genetic basis of chromosomal instability as it is a marker of genotoxic exposure and a predictor of cancer risk. For that purpose, we conducted two genome-wide association studies (GWASs) on healthy individuals in the presence and absence of apparent genotoxic exposure from the Czech Republic and Slovakia. The pre-GWAS cytogenetic analysis reported the frequencies of CSA, CTA and total CA (CAtot). We performed both linear and binary logistic regression analysis with an arbitrary cut-off point of 2% for CAtot and 1% for CSA and CTA. Using the statistical threshold of 1.0 × 10 −5, we identified five loci with in silico predicted functionality in the reference group and four loci in the exposed group, with no overlap between the associated regions. A meta-analysis on the two GWASs identified further four loci with moderate associations in each of the studies. From the reference group mainly loci within genes related to DNA damage response/repair were identified. Other loci identified from both the reference and exposed groups were found to be involved in the segregation of chromosomes and chromatin modification. Some of the discovered regions in each group were implicated in tumourigenesis and autism.